The Credit Process in Bulgaria After 1999: Some Macroeconomic Effects - Piperkov, Petar (Research Papers, 2025)
According to orthodox economic theory, the process of lending and credit creation has little or no macroeconomic significance. Various unorthodox theories reject this point of view in theoretical terms and point to an empirical relationship between lending and certain aggregated macrodynamics. This article examines lending to non-financial enterprises, households and NPISHs and its potential impact on the Bulgarian economy after 1999 in the light of these unorthodox theories, with the aim of testing their applicability and explanatory power. The object is the Bulgarian economy after 1999, and the subject matter is the dynamics of lending and selected macro-indicators. The scientific methods used are historical-logical analysis, comparative analysis and synthesis.
Keywords: Credit; Endogenous money; Real estate; Bad and restructured loans